Troublemakers, bystanders, and pathbreakers: The political participation of African youth - Resnick, Danielle (International Food Policy Research Institute, 2019)
Chapter 4 examines whether African youth are more politically engaged than their older counterparts, and to what extent their demands for political action are motivated by concerns about jobs and unemployment.